Effect of Using Educaplay Media in the Team Games Tournament (TGT) Model on Students’ Learning Outcomes - Nasya Amanda Nauvalia; Aswarina Nasution (Jurnal Pijar MIPA, 2026)
Science learning requires innovative strategies that actively engage students in the learning process. However, classroom learning is often still teacher-centered, resulting in low student participation and unsatisfactory learning outcomes. This study aimed to analyze the effect of using Educaplay media integrated with the Team Games Tournament (TGT) learning model on students’ learning outcomes in the topic of classification of living things. The research employed a quasi-experimental design with a nonequivalent control group. The sample comprised 62 seventh-grade students selected through purposive sampling, divided into an experimental and a control class. The experimental class received instruction using the TGT model assisted by Educaplay, while the control class used the TGT model without Educaplay. Data were collected using validated cognitive achievement tests and analysed using descriptive statistics, normality and homogeneity tests, and independent-samples t-tests. The results showed that the experimental class achieved a higher mean posttest score (74.35) than the control class (56.77). Hypothesis testing revealed a significance value (Sig. 2-tailed) of < 0.001 < 0.05, indicating that the use of Educaplay-assisted TGT significantly affected students’ learning outcomes. Therefore, integrating Educaplay with the TGT learning model can improve students’ engagement and science learning outcomes. These findings suggest that integrating Educaplay into cooperative learning can serve as an effective digital learning strategy to enhance student achievement and support more engaging science instruction in junior high schools.